Supervision of zemstvo sanitation on the living and working conditions of industrial workers in the Katerynoslav province - Arzamanov , Oleksiy (Skhid, 2023)
The article, within the framework of regional history, studies the problem of sanitary supervision of industrial workers who lived and worked in the territory of the Katerynoslav province of the Russian Empire. The role of Russian colonization in the life of the Ukrainian population has been evaluated. Working and living conditions of industrial workers and the most common sanitary problems that arose in their everyday life were revealed on the basis of the historical sources study of the Zemstvo of the Katerynoslav province. Positive and negative factors and results of cooperation between sanitary doctors and industrial workers are outlined. It is shown that a significant number of Russian industrialists who organized their enterprises in Ukrainian lands were not interested in providing decent living conditions for the workers of their enterprises, if this could hinder their profits. The practical task of the study is to expand the knowledge about the past of the ordinary inhabitants of the region, their contemporary life, to form in readers an idea of the historical development uniqueness of their own region within the framework of general Ukrainian history.